Overview and Prevalence of Eating Disorder in Post-Bariatric Surgery Patients: A Single Center Observational Study at Sumber Waras Hospital, Jakarta, Indonesia - Daniel Goh; Jeffrey; Lady Dhita Alfara (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: The prevalence of obesity continues to increase, and society needs to pay attention to it. One effective treatment that is also included in the pillars of obesity management is bariatric surgery. Apart from the many benefits of bariatric surgery, there are side effects that need to be considered, one of which is eating disorders. This study aims to determine the prevalence of eating disorders in post-bariatric surgery patients in Indonesia, especially at Sumber Waras Hospital, Jakarta. Methods. This research is a descriptive study with cross-sectional methods in post-bariatric surgery patients with a minimum BMI of 30 kg/m2. Results. A total of 54 patients after bariatric surgery at Sumber Waras Hospital, Jakarta filled out a questionnaire to assess tendencies towards eating disorders, namely EDE-Q 6.0 (Eating Disorder Examination Questionnaire) after 6 months of undergoing bariatric surgery. The results showed that 17 respondents (31.48%) experienced eating disorder tendencies. Conclusion. Eating disorders are one of the side effects of bariatric surgery that needs to be considered. Further research is still needed on this matter, considering the small number of samples in this study. Research on related topics is expected to expand its reach so might obtain a larger sample size.